Anatomy of Dissent: A Cultural Analysis of Climate Skepticism. (June 2013) - Lahsen, Myanna
Based on findings from ethnographic analysis of U.S. climate scientists, this article identifies largely unrecognized sociocultural dimensions underpinning differences in scientists' perceptions of anthropogenic climate change. It argues that culturally laden tensions among scientists have influenced some to engage with the antienvironmental movement and, as such, influence U.S. climate science politics. The tensions are rooted in broad-based and ongoing changes within U.S. science and society since the 1960s and propelled by specific scientific subgroups' negative experiences of the rise of environmentalism and of climate modeling, in particular. Attending to these and other experience-based cultural dynamics can help refine cultural theory and enhance understanding of the deeper battles of meaning that propel climate science politics.